2020
DOI: 10.1186/s12879-020-4779-4
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma and Strongyloides screening in migrants initiating HIV Care in Canada: a cross sectional study

Abstract: Background: Following migration from Schistosoma and Strongyloides endemic to non-endemic regions, people remain at high risk for adverse sequelae from these chronic infections. HIV co-infected persons are particularly vulnerable to the serious and potentially fatal consequences of untreated helminth infection. While general screening guidelines exist for parasitic infection screening in immigrant populations, they remain silent on HIV positive populations. This study assessed the seroprevalence, epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…A recent meta-analysis estimated a seroprevalence in immigrants from endemic areas and living in nonendemic areas at approximately 18%, with immigrants from sub-Saharan Africa having the highest prevalence (approximately 24%) [ 36 ]. The group of HIV + immigrants showed figures over 20% [ 37 ], and that of unaccompanied immigrant minors showed figures of approximately 16% [ 38 ]. In addition, in the immigrant group from endemic areas, approximately 40% of diagnosed infections occur in asymptomatic patients [ 8 ], which can cause a diagnostic delay [ 39 ] and sometimes has serious consequences [ 40 ].…”
Section: Chronic Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis estimated a seroprevalence in immigrants from endemic areas and living in nonendemic areas at approximately 18%, with immigrants from sub-Saharan Africa having the highest prevalence (approximately 24%) [ 36 ]. The group of HIV + immigrants showed figures over 20% [ 37 ], and that of unaccompanied immigrant minors showed figures of approximately 16% [ 38 ]. In addition, in the immigrant group from endemic areas, approximately 40% of diagnosed infections occur in asymptomatic patients [ 8 ], which can cause a diagnostic delay [ 39 ] and sometimes has serious consequences [ 40 ].…”
Section: Chronic Schistosomiasismentioning
confidence: 99%
“…The species most frequently implicated at this level is S. haematobium [ 37 ]. This is because S. haematobium , unlike other human-infecting schistosome species, mainly migrates to the veins surrounding the bladder (the vesicle venous plexus), thus causing urinary schistosomiasis [ 38 ].…”
Section: Urogenital Schistosomiasismentioning
confidence: 99%
“…2 This is a group with a high prevalence of infectious diseases, constituting a real public health problem for recipient countries. [3][4][5][6][7][8][9][10][11][12] To address this problem, several international organizations (European Center for Disease Prevention and Control; Migrant Health Assessment Sub-committee of Health Protection Surveillance Centre Scientific Advisory Committee. Infectious disease assessment for migrants 2015; The Committee to Advise on Tropical Medicine and Travel [CATMAT]) [13][14][15][16] have postulated the need for institutional screening programs that would contribute to early diagnosis and treatment of these pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious disease assessment for migrants 2015; The Committee to Advise on Tropical Medicine and Travel [CATMAT]) [13][14][15][16] have postulated the need for institutional screening programs that would contribute to early diagnosis and treatment of these pathologies. However, these recommendations have been made from estimates of previous epidemiological studies or have been based on the prevalence of different diseases in the country of origin, [3][4][5][6][7][8][9][10][11][12][13] which has often not been updated or showed contradictory results. Previous studies performed in countries of arrival showed variable prevalences of the different imported diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation